Efforts to Improve the Skills of Viewing Fables Using Fantasy Wayang Media in Class I SDN 2 Arjasari - Nurhayati, Diana Dewi; Rakhmat, Cece; Wakih, Agus Ahmad (Universitas Sebelas Maret, 2021)
This research is motivated by low listening skills, especially in fable stories. This study aims to improve listening skills to fable stories using fantasy puppet media. This type of research uses PTK with the first cycle using fable story “Friendship of the Lion and the Rat”, second cycle using the story of the fable “The Greedy Crocodile”. The technique of collecting data was by seeing the class teacher learning without using fantasy puppet media and giving 10 PG questions. The results showed an increase in listening skills the first cycle the number of students who received a complete score was 4 students with a percentage of 57% completeness, in the second cycle the number of students who received a complete score was 7 students with a percentage of 100% completeness. It was concluded that the fantasy puppet media used in reading fable stories could improve students listening skills.